2019
DOI: 10.37828/em.2019.21.1
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomic Revision of Fossil Freshwater Pearl Mussels (Bivalvia: Unionoida: Margaritiferidae) From Pliocene and Pleistocene Deposits of Southeastern Europe

Abstract: Margaritiferidae is an ancient freshwater bivalve family originated in the Jurassic in East Asia. Here, we revise several nominal taxa of fossil freshwater pearl mussels that were recovered from the Upper Pliocene and Pleistocene deposits of the Dniester and Prut river valleys. Based on morphological and stratigraphic data, we found that these nominal taxa belong to the genus Pseudunio and are junior synonyms of P. flabellatiformis (Grigorowitch-Beresowski, 1915). The new synonymy is proposed as follows: Marga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…However, a critical taxonomic revision of all these taxa is urgently needed to clarify their status, prospective phylogenetic placement, and validity. Multiple fossil species recovered from the Pleistocene deposits 98 should be compared with recent representatives of the corresponding genera, as many of these nominal taxa may be synonyms of terminal species or their stem lineages 33,101,102 .…”
Section: Biogeography Of the Unionidae In Russiamentioning
confidence: 99%
“…However, a critical taxonomic revision of all these taxa is urgently needed to clarify their status, prospective phylogenetic placement, and validity. Multiple fossil species recovered from the Pleistocene deposits 98 should be compared with recent representatives of the corresponding genera, as many of these nominal taxa may be synonyms of terminal species or their stem lineages 33,101,102 .…”
Section: Biogeography Of the Unionidae In Russiamentioning
confidence: 99%
“…Its larvae parasitize salmonids, the most suitable hosts for them being the brown trout and Atlantic salmon, and less suitable, the European taimen (see [83] and references therein). The extinct species M. arca Tshepalyga, 1964, which inhabited the Black Sea basin in the Upper Pliocene and Early Pleistocene, is considered to be the ancestor of M. margaritifera [84][85][86].…”
Section: Freshwater Pearl Mussels Of the Genus Margaritiferamentioning
confidence: 99%
“…However, the spread of cold-water aquatic organisms into the Mediterranean from the area of the present-day Black Sea in the later period (Neogene-Quaternary) was, apparently, difficult or even impossible. Most likely, this is why neither European taimen nor margaritiferid mussels parasitizing salmonids migrated to the Mediterranean, although both groups, according to paleontological data, already lived in the area of the modern Black Sea basin at that time [80,[84][85][86]. Our study of the mitochondrial COI gene diversity has demonstrated that the brown trout populations of the Black and Caspian seas are characterized by different groups of haplotypes, whereas the Mediterranean populations of this species have the haplotypes found in the Caspian basin (or those directly originating from them).…”
Section: The Routes Of the Spread Of Cold-water Species From The Paratethys To The Mediterranean Regionmentioning
confidence: 99%
“…The most common fluvial mussel, Pseudunio flabellatiformis, is well-known from the fluvial deposits of the Pannonian Basin throughout the entire late Miocene (as "Unio wetzleri" or "Margaritifera flabellatiformis" in the older literature; here we follow the revision of Lyubas et al 2019); thus, it does not constrain the age of FA5 and FA6 occurrences. In Derșida and in the lignite-bearing deltaic layers of Derna, however, Anancus arvernensis remains were found (Codrea and Margin 2009;Gasparik pers.…”
Section: Biostratigraphy and Agementioning
confidence: 99%